The Changes in Phosphorus Nutrient Levels and Growth of Mustard Greens (Brassica chinensis) in Sandy Soil Amended with Various Organic Materials - Waode Siti Anima Hisein; Awaluddin Awaluddin; Arsy Aysyah Anas; Yusran Yusran; Fahria Nadiryati Sadimantara; Siska Efendi (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Mustard greens (Brassica chinensis) are a high-potential horticultural crop in Indonesia, supported by rapid growth, strong market demand, and significant contributions to food security. This study examined the impact of various organic amendments on phosphorus (P) availability and plant growth in sandy soil. The experiment employed a two-factor Completely Randomized Design (CRD) with three types of organic material: cattle manure (B1), goat manure (B2), and Gliricidia sepium green manure (B3), and three application rates: 0% (D1), 10% (500 g polybag-⁻ ¹; D2), and 20% (1000 g polybag-⁻ ¹; D3). Each treatment combination was replicated three times, yielding 27 experimental units. Measured variables included P nutrient concentration, plant height, and leaf number. Data were analyzed using ANOVA, followed by Tukey's Honest Significant Difference (HSD) test to determine the most effective treatment for phosphorus nutrient levels and plant growth. The application of organic materials significantly increased P availability, with B3D3 yielding the highest concentration (21.03 ppm) and enhancing mustard green growth under sandy soil conditions.